2022
DOI: 10.1002/aenm.202200426
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Cycling Performance Enabled by Local Structural Rearrangements in Disordered Rocksalt Cathodes

Abstract: cost and thermal stability of Mn. [4] However, both families of cathodes face significant challenges in maintaining their structural integrity and rate capability upon cycling, with rapid capacity fade, significant voltage hysteresis, and impedance rise often accompanying the gradual transformation in local and/or long-range structure upon Li (de)intercalation. [5][6][7][8] At the material level, side reactions with the electrolyte, TM reduction and dissolution, TM migration and structural transformation as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 84 publications
(171 reference statements)
3
28
1
Order By: Relevance
“…One possible explanation is the formation of a spinel‐like phase upon extended cycling as was recently reported for other Mn‐based DRX cathodes. [ 22,47,48 ] Electron diffraction patterns collected on pristine and cycled LMTOF07 cathode (15 cycles) support this conclusion as shown in Figure S10 (Supporting Information). Notably, these changes are not observed in the LMTO04 and LMTOF05 compositions which maintain sloping voltage profiles after extended cycling.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…One possible explanation is the formation of a spinel‐like phase upon extended cycling as was recently reported for other Mn‐based DRX cathodes. [ 22,47,48 ] Electron diffraction patterns collected on pristine and cycled LMTOF07 cathode (15 cycles) support this conclusion as shown in Figure S10 (Supporting Information). Notably, these changes are not observed in the LMTO04 and LMTOF05 compositions which maintain sloping voltage profiles after extended cycling.…”
Section: Resultsmentioning
confidence: 59%
“…The superior cycling stability of LMTOF05, LMTOF06, and LMTOF07 is attributed to an increased contribution from Mn 3+ /Mn 4+ redox and therefore reduced dependence on oxygen redox. In LMTOF06 and LMTOF07, the increasing capacity with cycling may be due to the formation of spinel‐like phases with improved Li + diffusion and hence higher active material utilization, [ 47,48 ] although we note that additional characterization studies are needed to support this conclusion. In LMTOF07, although the discharge capacity increases over the first 50 cycles, it reaches a peak value of 275 mAh g −1 after 20 cycles before decreasing to 250 mAh g −1 after 50 cycles, with more rapid capacity fade upon extended cycling (Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 93%
“…It is well known that lithium transition metal oxides can form a rich variety of structures, depending on the physicochemical properties of the transition metal element, composition, and synthesis condition. Here, we briefly discuss the possibility of other types of Li–TM ordering in DRXs, considering that the Raman activity of rock salts can be activated by various mechanisms. In recent years, it has been reported that other types of short-range structural features can form in DRXs due to various reasons. ,,, A few of these works are based on Raman spectroscopic analyses. , For example, electrochemical cycling of Mn-rich DRXs has been shown to generate spinel-like cation arrangements. , To examine the role of cation arrangement in Raman spectroscopic features, we compared the Raman spectra of DRXs with other lithium transition metal oxide compounds. All of these compounds are based on an fcc or near-fcc oxygen sublattice.…”
Section: Resultsmentioning
confidence: 99%
“…37,41−43 For example, electrochemical cycling of Mnrich DRXs has been shown to generate spinel-like cation arrangements. 41,43 To examine the role of cation arrangement in Raman S15a. These compounds are also selected for comparison because cations in these compounds fully occupy the octahedral sites of the oxygen sublattice (1:1 cation/anion ratio), similar to LiCoO 2like layer-structured cathodes.…”
Section: Comparison Of Drxs With Other Lithium Transition Metal Oxide...mentioning
confidence: 99%
“…Then, the percolation of Li-ion is enabled by the continuous connection of the 0-TM local structures. The discovery of the Li-ion percolation mechanism has led to significant attention to the DRXs (Yabuuchi et al, 2016;Cai et al, 2021;Ahn et al, 2022;Pei et al, 2022;Zhou et al, 2022). However, many thresholds must be overcome for the commercialization of DRXs, such as low cyclic retention, wide operation voltage, and unsuitable synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%